Amazons : A Love Story - Levy, E. J. (Ellen J.) (Book collections on Project MUSE., 2012)
"When E.J. Levy arrived in northern Brazil on a fellowship from Yale at the age of 21, she was hoping to save the Amazon rain forest; she didn't realize she would soon have to save herself. Amazons: a love story recounts an idealistic young woman's coming of age against the backdrop of the magnificent rain forest and exotic city of Salvador"--Publisher's description.